Busca de Sentido da Vida e Reconciliação Cristã. Leitura teológica do pensamento de Viktor Frankl - Almeida, Nuno Manuel Santos (2017)
Seeking to bring together dynamically the pair ‘meaning of life’ and ‘Christian reconciliation’, my research presents the following as its main question: What relation can we establish between the meaning of life and Christian reconciliation? Note that the present text is just a summary of my doctoral dissertation in Dogmatic Theology, with the title: “Looking for the Meaning of Life and Christian Reconciliation. Theological reading of the thought of Viktor Frankl” (2016).